Dermocosmetics in dermatological practice. Recommendations of the Polish Dermatological Society. Part I - Barbara Zegarska; Lidia Rudnicka; Joanna Narbutt; Wioletta Barańska-Rybak; Beata Bergler-Czop; Ewa Chlebus; Magdalena Czarnecka-Operacz; Joanna Czuwara; Andrzej Kaszuba; Roman Nowicki; Agnieszka Owczarczyk-Saczonek; Waldemar Placek; et al. (Termedia Publishing House, 2023)
Dermocosmetics (active cosmetics, functional cosmetics, cosmeceuticals) are preparations for external use, supporting pharmacotherapy of skin diseases during the active phase of the disease and in remission. They are also used for healthy skin (preventive) care. Historically, topical skin care products have been divided into cosmetics and drugs, as defined by the Federal Food, Drug and Cosmetic Act of 1938. A cosmetic was defined as "articles intended to cleanse, care, beautify and improve the appearance of the skin". Drugs were defined as "products intended to affect the structure or any function of the body, or products intended for use in the diagnosis, treatment, mitigation, treatment or prevention of human diseases". Dermocosmetics (cosmeceuticals) remain cosmetics from a legal point of view, but they fill the gap between cosmetics and drugs. These products achieve a cosmetic effect with active substances however are not subject to drug regulations.